The Impact of Bureaucratic Reform Policy on Public Services at the Population and Civil Registration Service of North Padang Lawas Regency - Nasution, Adelina Fatmayanti; Sihombing, Marlon; Ridho, Hatta (Universitas Medan Area, 2024)
Based on an analysis of the bureaucratic conditions in North Padang Lawas Regency after more than 15 years as a new autonomous region, it appears that the quality of public services is still low. The evaluation of the Indonesian Ombudsman Representative for North Sumatra in 2021 placed the district in the